Downregulation of platelet activation markers during long-term immobilization. (August 2013) - Arinell, Karin; Fröbert, Ole; Blanc, Stéphane; Larsson, Anders; Christensen, Kjeld
<x xml:space="preserve">Abstract</x> Immobilization and sedentary lifestyle are risk factors for venous thromboembolism and cardiovascular disease, yet little is known about platelet function during long-term physical inactivity. Our aim was to investigate platelet activation markers and their coupling to standardized immobilization: platelet-derived growth factor (PDGF-BB) and P-selectin. We studied 15 healthy females participating in the Women International Space simulation for Exploration study. Following a 20-day ambulatory control period, the subjects underwent 60 days of bed rest in head-down tilt position (−6°) 24 hours a day, finalized by 20 days of recovery. The subjects were randomized into two groups during bed rest: a control group (n = 8) that remained physically inactive and an exercise group (n = 7) that participated in both supine resistance and aerobic exercise training. Blood samples for the analysis of platelet activation markers were collected at baseline (5 days before bed rest), after 44 days of bed rest and 8 days into the recovery period. Compared to baseline, the levels of P-selectin and PDGF-BB decreased after bed rest (by 55%, p = 0.01 and 73%, p < 0.03, respectively) and remained decreased in the recovery period (by 76%, p < 0.001 and 78%, p < 0.02, respectively, compared to baseline). Platelet count (baseline value for the exercise group 260 000/µl ± 34 000 and baseline value for the control group 210 000/µl ± 30 000) did not change during the bed rest study (two-way repeated measurements ANOVA, p = ns). There were no statistical differences between the physically inactive and the exercise group. During long-term immobilization, a known risk factor for thrombosis, the levels of P-selectin and PDGF-BB decreased. Our findings indicate downregulation of platelet activation during immobilization.